Self-Tuning Synthesis Filter against Mutual Coupling and Interferences for GNSS and Its Implementation on Embedded Board. (5th July 2010) - Chang, Chung-Liang
Abstract : Traditional spatial-temporal adaptive signal processing techniques are often applied to conduct narrowband and wideband interferences. However, its mitigation performance degrades greatly due to mutual coupling. To solve this problem, this paper aims to utilize a spatial-temporal self-tuning synthesis filter capable of mutual coupling compensation and interference mitigation. The spatial filter and temporal filter are to compensate for the effect of mutual coupling and interference mitigation, respectively. Self-tuning mechanism is to adopt least square (LS) and minimum variable distortionless response- (MVDR-) based method to adjust spatial and temporal weights of antenna array. The experiment platform is established by the embedded development board. Simulation and experiment results demonstrate that the proposed method can effectively compensate for mutual coupling, mitigate the cochannel interference up to 30 dB, and enhance the acquisition performance of receivers in global navigation satellite system (GNSS).